Intraovarian Platelet-rich Plasma Administration Induced Spontaneous Ovulation in an Anovulatory Woman With PCOS. Issue 2 (21st April 2023) - Merhi, Zaher; Mouanness, Marco; Wang, Ruoyu; Seckin, Serin
Abstract: The use of platelet-rich plasma (PRP) has become popular as an adjunct to fertility treatment for women with infertility, particularly those with low ovarian reserve and premature ovarian insufficiency. Recent data in a polycystic ovary syndrome (PCOS) animal model demonstrated that intraovarian PRP administration improved folliculogenesis, ovarian antioxidant potential, and serum hormonal imbalance, suggesting that PRP could be considered a novel technique to alleviate PCOS-induced pathogenesis. With injection of PRP into the ovaries, it has been hypothesized that the infusion of cytokines and growth factors may exhibit a local effect that changes the expression of genes important in folliculogenesis and steroidogenesis, decreases inflammation, and partially restores normal ovarian function. This report is the first to present a case of a long-term amenorrheic woman with PCOS who has been trying to conceive, who resumed spontaneous ovulatory cycles, and had improvement in several aspects of her hormonal imbalance following intraovarian PRP administration. The purpose of this case report is to increase awareness regarding the possible benefits of intraovarian PRP injections for women with PCOS. There is a clear need for larger prospective studies to properly elucidate the effect of intraovarian PRP administration on both the reproductive and metabolic dysfunctions observed in women with PCOS.